PB 13 Errors elicit high-gamma responses in the human cerebral cortex. Issue 10 (October 2017) - Völker, M.; Berberich, S.; Fiederer, L.D.J.; Hammer, J.; Kršek, P.; Tomášek, M.; Marusic, P.; Reinacher, P.C.; Coenen, V.A.; Schulze-Bonhage, A.; Burgard, W.; Ball, T.
Abstract : The nature of human error processing and the underlying cerebral mechanisms are of great interest in neuroscience, and error-related brain responses may provide information useful to improve the accuracy of brain-machine interfaces (BMIs). So far, many studies focused on error-related responses below 30 Hz. We were interested in error-related effects in the high-gamma band (HGB, 50–150 Hz), as this frequency range is thought to reflect local cortical information processing more directly than lower frequencies. 30 healthy subjects performed a flanker task as classically used to study error processing (Gehring et al., 1993 ). Under time pressure, the subjects had to use the left or right index finger to respond to the respective flanker. Recordings of 128-channel EEG were acquired within an optimized setting for non-invasive EEG high-gamma mapping in an electromagnetically shielded cabin with full optical decoupling of all devices and high-resolution binocular eye tracking. Additionally, 9 patients with pharmacoresistant epilepsy and implanted stereo-EEG (SEEG) electrodes performed the identical task. As our main result, we show for the first time error-related HGB spectral power modulations up to 120 Hz in non-invasive EEG (Fig. 1 A), which could also be used for decoding on a single-trial basis. Additional SEEG data (Fig. 1 B) revealed possible sources of these effects, including the premotor cortex. Additional responses were seen in areas not reflected in the non-invasive EEG, such as hippocampus and insula. Importantly, based on the eye-tracking data, we show that the error-related effects in the gamma range cannot be explained by differences in eye movements including micro-saccades, which had a different spatial distribution compared to the error-related effects. Our findings open a new window for investigation of the complex neuronal processes related to error perception and ensuing behavioral adaptation. The similarity of intracranial and non-invasive measurements further show that data of healthy subjects and epilepsy patients is comparable and physiological high-gamma activity can be found in both cases.